Uji Kelayakan E-LKPD Berbasis PBL (Problem Based Learning) Untuk Meningkatkan Keterampilan Proses Sains Peserta Didik SMA - Khairunnisa, Novia; Purwanto, Andik; Medriati, Rosane (Universitas PGRI Semarang, 2023)
This study aims to determine the validity of PBL (Problem Based Learning) based E-LKPD to improve the science process skills of high school students. By using the type of RD (Research and Development) method and consists of a process of (1) Analysis, (2) Design, and (3) Develop. This research instrument is a material expert validation sheet and a media expert validation sheet to determine the validity of E-LKPD. This study tested of E-LKPD with static electricity class XII material and was conducted at SMA Negeri 3 Bengkulu City, SMA Negeri 4 Bengkulu City, and SMA Negeri 9 Bengkulu City. Based on the data analysis that has been done, it is found that the results of the material E-LKPD validation are 88,3% with worthy criteria. While the results of media E-LKPD validation are 80% with worthy criteria. While the material reliability test results are 79% with reliable criteria and the media reliability test results are 94% with reliable criteria.Â So, it can be concluded that the PBL (Problem Based Learning) based E-LKPD to improve the science process skills of high school students is said to be worthy. Â Keywords: feasibility test of E-LKPD, PBL, Science Process Skills.